2018
DOI: 10.21272/jnep.10(5).05026
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Electrophysical Properties of Double-component Film Alloys Based on Molybdenum and Iron or Nickel

Abstract: The study of the structure-phase composition and electrophysical properties of film alloys of molybdenum and nickel or iron were deposited by the method of simultaneous thermo-vacuum condensation was done. In a non-annealing state, the samples remain biphasic. After heat treatment at 750 K in vacuum, the formation of the metastable phases of the fcc-Ni3Mo (lattice parameter a  0.360 nm) and bcc-Fe2Mo (a  0.296 nm) in film alloys based on Ni and Mo was recorded at concentrations of atoms of ferromagnetic meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…Obtained results are wellcorrelated with the results obtained by us and other authors in case of SiNW FETs [1-3, 7, 14-16] and FinFETs [3,4,7]. It should be noted that direct studies of the structure and phase states, electrophysical properties of thermal-stable bimetallic film alloys have been obtained by theauthors in [17][18][19][20]. The obtained results have shown that the studied structures can be used as gate contacts for CMOS (see, for example, [4]).…”
Section: Simulation and Resultssupporting
confidence: 86%
“…Obtained results are wellcorrelated with the results obtained by us and other authors in case of SiNW FETs [1-3, 7, 14-16] and FinFETs [3,4,7]. It should be noted that direct studies of the structure and phase states, electrophysical properties of thermal-stable bimetallic film alloys have been obtained by theauthors in [17][18][19][20]. The obtained results have shown that the studied structures can be used as gate contacts for CMOS (see, for example, [4]).…”
Section: Simulation and Resultssupporting
confidence: 86%
“…Based on these data and using the Atlas simulator, the main electrical parameters of photovoltaic converters are determined: open-circuit voltages UOC, short-circuit current densities JSC, maximum cathode current Im, maximum anode voltage Um, maximum power Pm, fill-factors FF, and photovoltaic efficiency  (Table 1), which are in good agreement with the experimental results of other authors [1][2][3][4][5][6][7]. Within the framework of the approach [17,19,20], the following equations are proposed to determine the temperature coefficients of the basic electrical parameters of solar cells.…”
Section: Simulation and Resultssupporting
confidence: 78%
“…In addition, in our works [10][11][12], the materials of transistor electrodes were analyzed in many aspectsfrom their manufacturing technology, structure, and electrophysical properties to the distribution of individual components in the gate in terms of effective output, and so on.…”
Section: -2mentioning
confidence: 99%